Challenges Faced by Teachers in Teaching Braille to Students with Visual Impairment (Journal of Asian Development Studies, 2024)
The current study investigated the challenges faced by the teaching faculty in teaching Braille to students with visual impairment. Students with visual impairment visual impairment face reading issues due to lack of their visual skills. Thereby, teachers of special education had to face various challenges while teaching Braille skills to their pupils with vision loss. The study ascertained these challenges to improvise the situation and resolve the reading issues of the students with visual problems. It was a descriptive study. A sample of forty teachers of special education currently teaching the pupils with visual problems in district Faisalabad, was selected for the study. The study sample was chosen on the basis of convenient sampling technique. A self-developed questionnaire with close ended nature of options was used to collect the data from respondents. Investigator himself approached the teaching faculty and collected the required data. The study findings showed that there was a very high level of inclination of the teachers (M=4.70) towards the factor that there was a lack of awareness and understanding about the Braille among other staff members, likewise teachers were struggling with time management issue while teaching Braille to the students with visual impairment. No any significant difference (p>0.05) between the male and female teachers challenges during Braille teaching was noted. The study will incorporate effective outcomes / information in teaching of Braille to the blind people, and help the special educators in handling the challenges while teaching Braille to students. It is recommended that teaching staff should be given special training regarding the use of Braille machine, including related services such as use of sixer, slate and stylus, Braille embosser, Braille software and other technological tools.